2018
DOI: 10.3389/fmicb.2018.02603
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Mechanisms of Lung Parenchymal Damage in Tuberculosis and the Role of Host-Directed Therapy

Abstract: Impaired lung function is common in people with a history of tuberculosis. Host-directed therapy added to tuberculosis treatment may reduce lung damage and result in improved lung function. An understanding of the pathogenesis of pulmonary damage in TB is fundamental to successfully predicting which interventions could be beneficial. In this review, we describe the different features of TB immunopathology that lead to impaired lung function, namely cavities, bronchiectasis, and fibrosis. We discuss the immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 194 publications
(246 reference statements)
0
63
0
2
Order By: Relevance
“…TIMPs are very important factors for TB disease, involved in tissue remodeling and repair upon destruction created by MMPs (17,18). Previous studies have identified MMPs as markers of disease severity, bacterial burdens and as a biomarker for disease in PTB and EPTB (17,(19)(20)(21). Relatively, few studies have focused on examining the circulating levels of MMPs and TIMPs as immune biomarkers in both PTB and EPTB.…”
Section: Introductionmentioning
confidence: 99%
“…TIMPs are very important factors for TB disease, involved in tissue remodeling and repair upon destruction created by MMPs (17,18). Previous studies have identified MMPs as markers of disease severity, bacterial burdens and as a biomarker for disease in PTB and EPTB (17,(19)(20)(21). Relatively, few studies have focused on examining the circulating levels of MMPs and TIMPs as immune biomarkers in both PTB and EPTB.…”
Section: Introductionmentioning
confidence: 99%
“…Current drug regimens are mainly directed at various targets on the Mtb bacillus [9,10]; this means that even after cure, TB patients are at risk of residual damage due to inflammatory effects (post TB fibrosis and bronchiectasis) [11]. Thus, supplementing anti-TB drug treatment with host immune modulators may lead to shorter treatment time, reduced lung damage, lower risk of relapse or reinfection and also improvement of other clinical outcomes [2,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressive state induced by HIV infection has been shown to hinder immune responses in tuberculosis infection affecting granuloma formation and fibrosis in HIV/tuberculosis co-infected patients. Hence, although these patients are at a higher risk of developing extrapulmonary tuberculosis (EPTB) (Mohammed et al, 2018), the extent of lung damage in pulmonary tuberculosis (PTB) is limited in them (Swaminathan et al, 2007;Stek et al, 2018). Furthermore the co-infected patients are at risk of developing TB-associated immune reconstitution inflammatory syndrome (TB-IRIS) in nearly half of the cases (48%) (Hattori et al, 2016;Lai et al, 2016) highlighting importance of understanding immunopathogenesis of this co-infection.…”
Section: Introductionmentioning
confidence: 99%